2015
DOI: 10.1038/cgt.2015.39
|View full text |Cite
|
Sign up to set email alerts
|

A 2015 update on predictive molecular pathology and its role in targeted cancer therapy: a review focussing on clinical relevance

Abstract: In April 2013 our group published a review on predictive molecular pathology in this journal. Although only 2 years have passed many new facts and stimulating developments have happened in diagnostic molecular pathology rendering it worthwhile to present an up-date on this topic. A major technical improvement is certainly given by the introduction of next-generation sequencing (NGS; amplicon, whole exome, whole genome) and its application to formalin-fixed paraffin-embedded (FFPE) tissue in routine diagnostics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 139 publications
(150 reference statements)
0
100
0
1
Order By: Relevance
“…Combining molecular information with histopathology and clinical staging, individual treatment strategies can be designed for maximum effectiveness 5, 14. Indeed, gene expression studies are accepted in human oncology as a validated method to discover biomarkers of disease and determine treatment options for example in lymphoma,15 breast,16 bladder cancers,17 sarcomas,18 and other tumor types 19. With the sequencing of the canine genome, similar biomarker strategies can be developed for veterinary diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…Combining molecular information with histopathology and clinical staging, individual treatment strategies can be designed for maximum effectiveness 5, 14. Indeed, gene expression studies are accepted in human oncology as a validated method to discover biomarkers of disease and determine treatment options for example in lymphoma,15 breast,16 bladder cancers,17 sarcomas,18 and other tumor types 19. With the sequencing of the canine genome, similar biomarker strategies can be developed for veterinary diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer experiments, the malignant phenotypes represent a variety of possible detections obtainable in multiple ways. Hundreds of genes are currently targeted, but only a few are actionable, i.e., effectively and/or successfully "drugged" according to approved drugs (Alyass et al, 2015;Dietel et al, 2015). Then, different marker types will become central to future analyses, from prognostic markers (focused on disease outcomes) to predictive markers (focused on identifying patient sub-groups responsive to specific treatments).…”
Section: Role Of High-throughput Genomicsmentioning
confidence: 99%
“…Zhao et al [40] published their observations in 2009 and showed that the mutations (IDH1 R132 or IDH2 R172) reduce the affinity of the enzyme toward the substrate and, moreover, inactive heterodimers which dominantly block the WT-IDH1 activity. The rapid understanding of the molecular pathways of the pathogenesis of brain tumors especially in glial tumors led to the detection of reliable diagnostic, prognostic and predictive molecular markers and new molecular signatures [41]. Three molecular markers, namely 1p19q co-deletion, MGMT promoter methylation mutation and mutation in IDH1/2 genes, stand out in the management of disease course and surgical neuropathology routine at the basis of various clinical trials.…”
Section: Molecular Pathological Assessment In Glial Tumorsmentioning
confidence: 99%